INOVASI PEMBELAJARAN BAHASA INGGRIS BERBASIS ICT DALAM RANGKA MENINGKATKAN MUTU PENDIDIKAN - Faridi, Abdurracman (Universitas Negeri Semarang, 2009)
It is an undeniable fact that most of our students nowadays can enjoy havingnew technology either at homes or at schools. For this, it is quite possible for them tohave ICT for learning. The purpose of having this kind of method is that students willhave two advantages at the same time, i.e. the linguistic aspects and the content. Forthe linguistic aspects, firstly, they will learn the English sound system throughspelling, secondly the grammar, by combining words into longer utterances, andfinally the choice of words or vocabulary. While for the content, ICT let the studentslearn (assisted by the teacher) the variety of language used within a certain subject.Teaching technique using chalk and talk or explanation is not popular anymore. It isthen suggested that the teacher uses internet within his teaching learning process and itis also compulsory for the students to learn to use it. The Internet is a must, because itcan be used (1) as the source of knowledge (2) as an aid for learning (instructional aid)(3) as teaching or learning facility (4) as a standard of competency (5) as anadministrative equipment (6) as a supporting equipment for the school management(7) as an educational infrastructure. Beside the aforementioned aspects, there areadditional factors to consider. Among others are (a) the environmental factor whichconsists of school or institution holding the activity (b) students who learn, their ages,social and economical background, the language and literacy of IT, the variety oflearning (c) the teacher, consists of the background of the teacher, the age, theteaching style, the experience and the personality (d) factors of technology whichconsists of computer, software, internet network and other application of EducateNetat schools.Kata kunci: ICT, standar kompetensi, infrastruktur, literatur, jaringan internet